THE IMPLEMENTATION OF GENRE-BASED APPROACH IN AN EFL CONTEXT - Efendy, Yusuf (2006)
This descriptive qualitative case study is intended to describe the implementation of genre-based approach in an EFL context. There are four issues posed in the study. The first is how the teacher prepared the teaching materials for classroom instructional practices. The second is how the teacher conducted the instructional practices in the classrooms. The third is how the teacher evaluated the students' learning achievement, and the last is what the teacher understood of Genre Based Approach.Data were collected through classroom observations, interviews, and survey of documents. This research began with conducting pre-observation, followed by intensive observations. Interviews were conducted both in order to examine the reasons behind the activities that the teacher did during observations and in order to find the teacher's understandings of Genre Based Approach. Documents were examined to see if the teacher prepared the lesson based on the curriculum. The data were analyzed inductively.It is found that 1) the teacher selected the materials from various sources 2) the teacher partially did what genre based approach recommended, i.e. it was not in right orders, 3) the teacher evaluated the students' learning both during and after teaching learning process, and 4) although at the surface level, the teacher knew and understood what is meant by genre and genre based approach.